Biochemical quality assessment of fourteen selected dried fish - Azam, K; Basher, MZ; Asaduzzaman, M; Hossain, MM; Ali, MY (University Journal of Zoology, Rajshahi University, 2007)
Key words: Dry fish; total volatile basic nitrogen; tri-methyl amine; pH Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 23-26